Peran Kepemimpinan Kepala Sekolah dalam Pengelolaan Budaya dan Lingkungan Sekolah Berbasis Karakter: Studi Kasus di UPT SMP Negeri 17 Medan - Hasibuan, Siti Fadillah; Lestari, Wilda; nasution, jamila; Ambarita, Mela E; Amalia, Nadra (eScience Humanity Journal, 2025)
This study aims to describe the role of principal leadership in managing school culture and environment based on character education at UPT SMP Negeri 17 Medan. The research employed a qualitative descriptive method with data collection techniques including in-depth interviews and participatory observation. The research subject was the Vice Principal of UPT SMP Negeri 17 Medan. The results showed that the principal carries out a holistic leadership role through the implementation of positive habituation programs such as greeting, smiling, and saluting culture, routine religious activities (Friday religious activities and reciting together), and religious-based extracurricular coaching. School environment management is carried out comprehensively covering physical, social, and psychological dimensions by providing supporting infrastructure and creating an inclusive atmosphere that fosters students' sense of belonging to the school. The main obstacles faced are lack of support from family environment and budget limitations. The solutions implemented are parenting programs and collaboration with stakeholders. Positive impacts are seen from a drastic decrease in student delinquency cases, increased teacher professionalism, and improved school performance. This research reinforces transformational leadership theory in the context of character education, where the principal functions as a change agent who inspires and empowers all school members to achieve optimal character formation goals.